Rethinking the Atlantic world : Europe and America in the age of democratic revolutions - Albertone, Manuela, 1953-; De Francesco, Antonino, 1954- (Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2009)
"The new Atlantic history has hitherto focused predominantly on the British Atlantic Empire. This volume, by contrast, explores intellectual history and political processes during the final democratic revolutions of the eighteenth century, while questioning the centrality of the area ruled over by Britain and America. It re-examines the role played by continental Europe and the connections between various national cultures. Rethinking the Atlantic World shows how ideas rebounded across the Atlantic, how they were received, and how they combined and gave rise to new ideas and new political action. Consequently, it places the French Revolution firmly at the heart of Atlantic history, but from a perspective which transcends the ideological limits imposed by twentieth-century debate."--BOOK JACKET.
Political ideas and economic models in eighteenth-century Europe and America. The one and the many : the two revolutions question and the 'consumer-commercial' Atlantic, 1789 to the present / Allan Potofsky - - Democracy and equality in the radical Enlightenment : revolutionary ideology before 1789 / Jonathan Israel - - Between republicanism and the Enlightenment : Turgot and Adams / Maria Luisa Pesante - - Nicolas Bergasse and Alexander Hamilton : the role of the judiciary in the separation of powers and two conceptions of constitutional order / Pasquale Pasquino - - Neutrality and trade in the Dutch republic (1775-1783) : preludes to a piecemeal revolution / Koen Stapelbroek - - Free trade and democratic revolutions in eighteenth-century Europe and America. Thomas Jefferson and French economic thought : a mutual exchange of ideas / Muanuela Albertone - - The question of slavery in the physiocratic texts : a rereading of an old debate / Marcel Dorigny - - 'A new kind of federalism' : Benjamin Constant and modern Europe / Biancamaria Fontana - - Industry, government and Europe : from the mercantilists to Saint-Simon / Gino Longhitano - - The American and the French revolutions : from two continents a new political world. France and the United States at the end of the eighteenth century / James Roger Sharp - - The French and North American revolutions in comparative perspective / Richard Whatmore ; Federalist obsession and Jacobin conspiracy : France and the United States in a time of revolution, 1789-1794 / Antonino de Francesco - - In search of the Atlantic republic : 1660-1776-1799 in the mirror / Pierre Serna - - The republican imagination and race : the case of the Haitian revolution / Bernard Gainot.
Includes bibliographical references and index.
Keywords: Europe -- History -- 18th century; United States -- History -- 18th century; Europe -- Politics and government -- 18th century; United States -- Politics and government -- 18th century; Europe -- Foreign relations -- United States; United States -- Foreign relations -- Europe; Europe -- Intellectual life -- 18th century; United States -- Intellectual life -- 18th century